2008
DOI: 10.1016/j.jconrel.2008.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer to hemophilia A mice via oral delivery of FVIII–chitosan nanoparticles

Abstract: Effective oral delivery of a non-viral gene carrier would represent a novel and attractive strategy for therapeutic gene transfer. To evaluate the potential of this approach, we studied the oral gene delivery efficacy of DNA polyplexes composed of chitosan and Factor VIII DNA. Transgene DNA was detected in both local and systemic tissues following oral administration of the chitosan nanoparticles to hemophilia A mice. Functional factor VIII protein was detected in plasma by chromogenic and thrombin generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 47 publications
(50 reference statements)
2
44
3
Order By: Relevance
“…The uses of chitosan as cationic complexing agent and as coating polymer have been extensively studied for oral drug delivery systems (9,17,34). As coating agent, the chitosan polymer decreased the chance of lipid vesicles to be attacked by enzymes.…”
Section: In Vivo Study Of Chitosan-coated Liposomes Carrying Gfpmentioning
confidence: 99%
“…The uses of chitosan as cationic complexing agent and as coating polymer have been extensively studied for oral drug delivery systems (9,17,34). As coating agent, the chitosan polymer decreased the chance of lipid vesicles to be attacked by enzymes.…”
Section: In Vivo Study Of Chitosan-coated Liposomes Carrying Gfpmentioning
confidence: 99%
“…Local expression of therapeutic proteins may have therapeutic benefit in the treatment of inflammatory bowel disease, intestinal cancer, and the intestinal symptoms of cystic fibrosis (O' Neill et al 2011) (Page and Cudmore 2001). Furthermore, the intestine can potentially provide a route of entry into the bloodstream for locally expressed therapeutic proteins such as Factor VIII in haemophilia patients (Bowman et al 2008), or indeed for gene therapies to distant disease sites.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan-DNA NP are of increasing interest as a nonviral gene carrier system (5,6,27). Using chitosan-DNA NP for oral application, exploiting oral tolerance mechanisms, would allow the development of DNA-based tolerogenic vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan has been complexed with plasmid DNA, forming chitosan-DNA nanoparticles (NP), which are stable during the gastrointestinal passage and will be phagocytized in the gut, resulting in gene expression (2). It was shown that feeding of factor VIII-encoding chitosan-DNA NP to hemophilia A mice resulted in increased factor VIII plasma levels (6,15) and that oral application of erythropoietin-encoding chitosan-DNA NP led to a significant increase of hematocrit levels (8). In rodent models of diabetes, chitosan-DNA NP encoding insulin or glucagon-like peptide 1 were able to decrease blood glucose concentrations (23,31,32).…”
mentioning
confidence: 99%